Effectiveness and Outcomes of Fishing Gear Assistance on Fishermen's Income in Pedes District Karawang - Ikhlasul Akbar; Kuswarini Sulandjari; Fatimah Azzahra (UNIVED Press, Dehasen University Bengkulu, 2023)
Fishing gear assistance is one of a series of activities undertaken by the Ministry of Marine Affairs and Fisheries by providing fishing gear, Gill Net and Trammel Net to fishermen. The study aims to analyse the level of effectiveness of activities, analyze the strength of supportive and inhibitory factors that influence, and analyse the outcome of fishing gear assistance on fishermen's reception. The research method used is quantitative descriptive. Primary data collection is obtained directly through questionnaires and interviews whereas secondary data is acquired through journal literacy and related scripts as well as data from related agencies. Sampling was done with a census of 40 fishermen. Data analysis on this study uses the likert scale, the guttman scale and the t test. The results of this study show that the overall distribution of aid is running effectively. Both supportive factors have strong influence and both inhibitory factors have weak influence in the distribution of aid. There has been a change in fishermen's reception before and after the distribution of fishing gear with a sig. (2-tailed) value of 0,000 < 0,05, whereas fisherman recipient of shrimp net assistance has not experienced any change in reception after the assistance of fish gear.